Prevalence of exclusive breastfeeding and barriers for its continuation up to six months in Kandy district, Sri Lanka - Himali Erandathie Ratnayake; Dhammica Rowel (BMC, 2018)
Abstract Background Since 2005, the national policy on breastfeeding in Sri Lanka is exclusive breastfeeding up to 6 months, as recommended by World Health Organization. The objective of this study was to assess the prevalence of exclusive breastfeeding and barriers for its' continuation up to 6 months, in Kandy District, Sri Lanka. Methods A clinic based cross-sectional study was conducted from August to November 2016, in six randomly selected Medical Officer of Health areas in the Kandy District. The sample was selected proportionate to the population of each Medical Officer of Health area and 354 mothers with infants aged 6 months, attending the child welfare clinics were recruited. Data were collected by an interviewer administered questionnaire using mother recall data since birth. A focus group discussion was conducted on 21 mothers who discontinued exclusive breastfeeding early. The infant taking only breast milk and no additional food, water, or other fluids with the exception of medicines and vitamins or mineral drops for the first 6 months was used as the definition of exclusive breastfeeding. Results The prevalence of exclusive breastfeeding for 6 months was 50.8% (180/354) while the median duration was 6 months. Mother being employed (AOR 3.01; 95% CI 1.45, 6.29), mother's poor knowledge on what she meant by exclusive breastfeeding (AOR 3.75; 95% CI 2.14, 6.54) and mother's poor attitudes towards exclusive breastfeeding (AOR 2.98; 95% CI 1.76, 5.03) were independently associated with early cessation of exclusive breastfeeding. Unsupported environment in public places was not significantly associated with early cessation of exclusive breastfeeding. Focus group discussion revealed controversial health messages on exclusive breastfeeding delivered at different points of healthcare delivery, cultural practices which discouraged exclusive breastfeeding and difficulties in obtaining maternity leave as barriers for exclusive breastfeeding. Conclusions The prevalence of exclusive breastfeeding up to 6 months was not satisfactory and there were barriers identified in healthcare system, family and work places towards exclusive breastfeeding. For further improvement in the prevalence of exclusive breastfeeding these issues need to be addressed and necessary changes in legislation implemented.